E-PARTICIPATION IN THE MANAGEMENT OF TOBACCO EXCISE PRODUCTION SHARING FUNDS: AN INITIATION TO STRENGTHEN THE PRINCIPLES OF DECENTRALIZATION IN INDONESIA - Aditya Wirawan; Retno Saraswati; Nabitatus Sa’dah; Reny Yemimalina Sinaga (Scientia Integritas Utama, 2022)
The implementation of the Tobacco Excise Production Sharing Fund (Dana Bagi Hasil Cukai Hasil Tembakau/DBHCHT) still leaves a disharmony between justice and public benefit, considering that even though the revenue from tobacco excise revenue has increased, the allocation has not been able to cover losses in several impovitalas of the state, such as the field of community welfare, law enforcement, and health on the justification for the less control of cigarettes in society on behalf of excise levies on tobacco products. Two main conclusions were drawn based on a normative juridical study with a focusing principle of decentralization. First, there are still several obstacles and challenges in the management of DBHCHT in Indonesia due to the inadequate participation of the stakeholders involved in the implementation of DBHCHT. Second, e-participation, which includes e-information, e-consultation, and e-cooperation, is needed so that the performance of DBHCHT management in Indonesia can run ideally based on the principle of decentralization. Even though the private industry holds the cigarette trade, it is compulsory to transfer the actual CHT as the mandate of decentralization principle in the 1945 Constitution due to the DBHCHT that local governments must accept in carrying out their functions and duties to develop their regions. It is recommended that the central government build an online DBHCHT system, including a website, to accommodate the running of e-participation so that decentralization in the implementation of DBHCHT produces the expected outputs and outcomes.